The Role of Digital Transformation and Leadership Style on Financial Performance of Defense Industries - Kurniawan, Wahyudi; Soediantono, Dwi (AGUSPATI Research Institute, 2022)
The purpose of this study is to analyze the influence of the managers' leadership style and digital transformation on financial performance on defense industries. The method used in this research is quantitative and uses SEM (Structural Equation Modeling), and data analysis uses SmartPLS 3.3.3 software. The population in this study was 130 staff of defense industries. The sampling technique used is cluster random sampling, and the data collection method used is a survey through filling out a questionnaire. Based on data analysis, we conclude that leadership style has a significant effect on financial performance. This means that an effective leadership style will increase financial performance and an ineffective leadership style will decrease financial performance. Digital transformation has no significant effect on financial performance. This means that an increase in digital transformation will not increase financial performance and a decrease in digital transformation will not decrease financial performance. Leadership style has a significant effect on digital transformation. This means that an effective leadership style will increase digital transformation and an ineffective leadership style will decrease digital transformation. The novelty of this research is the creation of a variable model of leadership style, digital transformation, and financial performance in defense industries